Unemployment Persistence and Capital Shortage : The Case of Trinidad and Tobago - Braumann, Benedikt (IMF Working Papers; Working Paper, 1997)
This paper examines the link between capital stock and unemployment persistence. An overlapping-generations model with endogenous labor supply and imperfect competition is presented. It is used to interpret the unusual persistence of unemployment in Trinidad and Tobago during the last twenty years. Although real wages are 60 percent lower today than in the mid-1980s, unemployment continues to be very high. The paper argues that an important part of the explanation lies in the decline of capital stock in this country after years of very low savings and investment. Policies to address this capital shortage are discussed.